Brassica rapa BrICE1 and BrICE2 Positively Regulate the Cold Tolerance via CBF and ROS Pathways, Balancing Growth and Defense in Transgenic Arabidopsis - Wangze Wu; Haobo Yang; Peng Xing; Guoting Zhu; Xueyan Han; Mei Xue; Guotai Min; Haijun Ding; Guofan Wu; Zigang Liu (Plants, 2024)
Winter rapeseed (Brassica rapa) has a good chilling and freezing tolerance. inducer of CBF expression 1 (ICE1) plays a crucial role in cold signaling in plants; however, its role in Brassica rapa remains unclear. In this study, we identified 41 ICE1 homologous genes from six widely cultivated Brassica species. These genes exhibited high conservation, with evolutionary complexity between diploid and allotetraploid species. Cold stress induced ICE1 homolog expression, with differences between strongly and weakly cold-tolerant varieties. Two novel ICE1 paralogs, BrICE1 and BrICE2, were cloned from Brassica rapa Longyou 6. Subcellular localization assays showed that they localized to the nucleus, and low temperature did not affect their nuclear localization. The overexpression of BrICE1 and BrICE2 increased cold tolerance in transgenic Arabidopsis and enhanced reactive oxygen species’ (ROS) scavenging ability. Furthermore, our data demonstrate that overexpression of BrICE1 and BrICE2 inhibited root growth in Arabidopsis, and low temperatures could induce the degradation of BrICE1 and BrICE2 via the 26S-proteasome pathway. In summary, ICE1 homologous genes exhibit complex evolutionary relationships in Brassica species and are involved in the C-repeat/DREB binding factor (CBF) pathway and ROS scavenging mechanism in response to cold stress; these regulating mechanisms might also be responsible for balancing the development and cold defense of Brassica rapa.